Innovation Of Mobile Virtual Laboratory As a Learning Facility - Sabirin, Febrianto; Marlianto, Ferry; Sulistiyarini, Dewi; Saputro, Marhadi (STKIP Singkawang, 2025)
The presence of Informatics subjects is a response to preparing human resources (HR) who can adapt to the industrial revolution 4.0 and society 5.0. Unfortunately, there are obstacles in implementation, especially related to computer laboratory facilities. So innovation is needed that can help schools implement Informatics subjects so that students can have adequate digital literacy in facing the industrial revolution 4.0 and society 5.0. The aim of the research is to develop and test the feasibility of being an Informatics learning facility for high school students in Pontianak City, as well as seeing the students' response to the mobile virtual laboratory. The method used is Research and Development (R&D), with a development design using DDD-E. Research subjects consist of development subjects, namely design experts, media experts and material experts and students to determine the response to the media being developed. Data analysis techniques use a data analysis approach Qualitative and quantitative. The results of the research are that the media was developed using DDD-E, the suitability of the media based on material experts and media experts is in the very good category and suitable for use. Student responses to the media that have been developed are very good for use.